TOURISM SERVICES’ REGULATION IN THE PROCESS OF UZBEKISTAN’S ACCESSING THE WTO: LEGAL AND PRACTICAL ANALYSES (TSUL LEGAL REPORT, 2026)
Today, the World Trade Organization is the main foundation of all economic activity in globalized states. The membership of the Republic of Uzbekistan in this organization will create the responsibility for a comprehensive analysis of the issues of its membership in the future, which will play an important role in the further integration of the country into the world community. The General Agreement on Trade in Services, as an integral treaty of this system, is considered to be one of the important agreements. The research paper emphasizes the legal and practical aspects of the regulation of tourism services in the framework of the GATS during this accession process. Moreover, recommendations based on international-legal norms on the WTO, scientific sources, and the results of in-depth interviews with foreign and national professionals, as well as academicians, which should be implemented in the conditions of Uzbekistan’s joining the organization have been proposed.